The implications of American chestnut reintroduction on landscape dynamics and carbon storage. Issue 4 (3rd April 2017) - Gustafson, Eric J.; de Bruijn, Arjan; Lichti, Nathanael; Jacobs, Douglass F.; Sturtevant, Brian R.; Foster, Jane; Miranda, Brian R.; Dalgleish, Harmony J.
Abstract: In the eastern United States, American chestnut ( Castanea dentata ) was historically a major component of forest communities, but was functionally extirpated in the early 20th century by an introduced pathogen, chestnut blight ( Cryphonectria parasitica ). Because chestnut is fast‐growing, long‐lived, and resistant to decay, restoration of American chestnut using blight‐resistant stock could have the potential to increase carbon sequestration or storage in forested landscapes. However, carbon dynamics are also affected by interspecific competition, succession, natural disturbance, and forest management activities, and it is unknown how chestnut restoration might interact with these other processes. We used the PnET‐Succession extension of the LANDIS‐II forest landscape model to study the implications of chestnut restoration on forest composition and carbon storage in the context of other disturbances, including timber harvest and insect pest outbreaks. Our results imply that it could take a millennium or more for chestnut to fully occupy landscapes without aggressive restoration efforts. When successful, chestnut restoration activities displaced other species approximately in proportion to their abundance on the landscape, rather than replacing a single species or genus (e.g., Quercus ). Insect pests increased the rate of chestnut colonization by reducing the abundance of competitors, and also had a dominant effect on carbon dynamics. Although chestnut is fast‐growing, moderately shade‐tolerant, and decomposes very slowly, our results suggest that it can only modestly increase the carbon storage potential of eastern forests. However, our results also demonstrate that compositional changes in forest communities can have noticeable effects on biomass accumulation, even with the large uncertainties introduced by invasive pests.